Combatting acquired resistance to osimertinib in EGFR-mutant lung cancer. (December 2022) - Lee, Jiyun; Piotrowska, Zofia; Soo, Ross; Cho, Byoung Chul; Lim, Sun Min
The discovery of activating mutations in epidermal growth factor receptor (EGFR) in non-small-cell lung cancer transformed the care and prognosis of patients and heralded the era of 'personalized medicine' in thoracic oncology. Osimertinib, a third-generation EGFR inhibitor, has been established as the preferred EGFR inhibitor for newly diagnosed patients which urged the need to develop treatment options for patients progressing on first-line osimertinib. However, acquired resistance invariably emerges and numerous efforts have been attempted to delay or overcome acquired resistance. In this article, we thoroughly reviewed the current understanding of osimertinib resistance mechanisms and explored the established and emerging treatment options. Newer treatment strategies targeting EGFR-dependent or -independent resistance mechanisms, novel approaches using bispecific antibodies and antibody–drug conjugates will be discussed. Moreover, what to do with brain only progression, and how to incorporate immunotherapy in EGFR-mutant lung cancer will be discussed. Lastly, future perspectives on the ongoing clinical trials and combination of front-line therapy will be introduced.